Incidence and Progression of Coronary Artery Calcium in South Asians Compared With 4 Race/Ethnic Groups - Kanaya, Alka M.; Vittinghoff, Eric; Lin, Feng; Kandula, Namratha R.; Herrington, David; Liu, Kiang; Blaha, Michael; Budoff, Matthew J. (Journal of the American Heart Association, 2019)
Background South Asians have a relatively high prevalence of coronary artery calcium ( CAC ) compared with other race/ethnic groups. We determined CAC incidence and progression among South Asians, and compared them with 4 race/ethnic groups. Methods and Results Data from the MASALA (Mediators of Atherosclerosis in South Asians Living in America) study were used to calculate CAC incidence and progression rates and any CAC change. Data from the MESA (Multi-Ethnic Study of Atherosclerosis) were used to compare the CAC incidence and progression rates. A total of 698 South Asians had repeat CAC measurements after 4.8±0.8 years. Among those with no CAC at baseline, the age-adjusted CAC incidence was 8.8% (95% CI, 6.8-10.8%) in men and 3.6% (2.5-4.8%) in women. The median annual CAC progression was 26 (interquartile range, 11-62) for men and 13 (interquartile range, 4-34) for women. Compared with MESA , age-adjusted CAC incidence was similar in South Asian men compared with white, black, and Latino men, but significantly higher than Chinese men (11.1% versus 5.7%, P=0.008). After adjusting for age, diabetes mellitus, hypertension, and statin medication use, Chinese, black, and Latino men had significantly less CAC change compared with South Asian men, but there were no differences between South Asian and white men. There was no difference in CAC incidence or progression between South Asian women and women in MESA . Conclusions South Asian men had greater CAC change than Chinese, black, and Latino men but similar change to that of whites after adjusting for traditional risk factors.